Population-based study of risk and predictors of stroke in the first few hours after a TIA. - Chandratheva, A; Mehta, Z; Geraghty, O; Marquardt, L; Rothwell, P (2009)
BACKGROUND: Several recent guidelines recommend assessment of patients with TIA within 24 hours, but it is uncertain how many recurrent strokes occur within 24 hours. It is also unclear whether the ABCD2 risk score reliably identifies recurrences in the first few hours. METHODS: In a prospective, population-based incidence study of TIA and stroke with complete follow-up (Oxford Vascular Study), we determined the 6-, 12-, and 24-hour risks of recurrent stroke, defined as new neurologic symptoms of sudden onset after initial recovery. RESULTS: Of 1,247 first TIA or strokes, 35 had recurrent strokes within 24 hours, all in the same arterial territory. The initial event had recovered prior to the recurrent stroke (i.e., was a TIA) in 25 cases. The 6-, 12-, and 24-hour stroke risks after 488 first TIAs were 1.2% (95% confidence interval [CI]: 0.2-2.2), 2.1% (0.8-3.2), and 5.1% (3.1-7.1), with 42% of all strokes during the 30 days after a first TIA occurring within the first 24 hours. The 12- and 24-hour risks were strongly related to ABCD2 score (p = 0.02 and p = 0.0003). Sixteen (64%) of the 25 cases sought urgent medical attention prior to the recurrent stroke, but none received antiplatelet treatment acutely. CONCLUSION: That about half of all recurrent strokes during the 7 days after a TIA occur in the first 24 hours highlights the need for emergency assessment. That the ABCD2 score is reliable in the hyperacute phase shows that appropriately triaged emergency assessment and treatment are feasible.